Keystroke Dynamic and Graphical Authentication Systems - Tenreiro De Magalhaes, Sérgio (2015)
In information systems, authentication involves, traditionally, sharing a secret with the authenticating entity and presenting it whenever a confirmation of the user’s identity is needed. In the digital era, that secret is commonly a user name and password pair and/or, sometimes, a biometric feature. Both present difficulties of different kinds once the traditional user name and password are no longer enough to protect these infrastructures, the privacy of those who use it, and the confidentiality of the information, having known vulnerabilities, and the second has many issues related to ethical and social implications of its use. This chapter discusses two behavior biometric technologies.